Cultural and Tradition Managemen Cultural and Tradition Management Model : A Study of the Meaning of Friday Pahing in Purworejo Village, Suruh District, Semarang Regency - Erwanto Guntoro; Siti Ruqoyyah; Albert Efendi Pohan (Institute of Educational, Research, and Community Service)
The Friday Pahing tradition is one of the local wisdoms that is still preserved by the people of Purworejo Village, Suruh District, Semarang Regency. This tradition not only has spiritual value, but also plays a role in strengthening the social and cultural identity of the local community. This study aims to analyze the meaning of the Friday Pahing tradition and explore the cultural management model applied in its preservation. A qualitative approach with an ethnographic study method is used to understand the dynamics of this tradition from the perspective of the local community. The results of the study show that the Friday Pahing tradition has three main dimensions, namely religious, social, and economic values. In terms of management, the preservation of this tradition involves the role of traditional leaders, religious figures, and the community through a pattern of cultural transmission that is hereditary. The cultural management model applied is adaptive, where this tradition continues to exist despite facing the challenges of modernization. This study confirms that the sustainability of local traditions is highly dependent on the active participation of the community and support from various parties in efforts to preserve it.